Determining Moral Value in Movies: An Analysis of the Movie “Onward” - Ayuni, Putri Qurota (Raden Intan State Islamic University of Lampung, Indonesia, 2023)
Recent trends indicate a discernible decrease in the perceived significance of education, particularly among the adolescent and student demographic. The observed phenomenon can be attributed to a potential lack of parental emphasis on cultivating educational values in their offspring during early developmental stages, particularly in the contemporary era. The acquisition of knowledge through the guidance of teachers primarily centers on the assimilation of academic content, with limited attention given to examining potential moral decline among educators. The mitigation of this issue necessitates the active involvement of educators. Educators necessitate a medium that possesses the capacity to facilitate the instruction of various subjects, all the while ensuring that it imparts educational worth to the students. One of the forms of media that has gained significant popularity and cultural influence is the medium of film, commonly referred to as movies. The present study aims to explore and analyze the moral value embedded within the animated film titled